The Influence of Accounting Vocational Competence On Work Readiness With Self-Efficacy As a Mediating Variable At Sunan Giri Menganti Vocational School - Esa Puspa Arini; Eko Wahjudi (JURNAL PENDIDIKAN IPS, 2025)
Accounting expertise competencies among students of SMK Sunan Giri Menganti for the 2022/2023 and 2023/2024 academic years have declined significantly each year. In response to this condition, this study aims to examine how accounting expertise competencies influence work readiness, with self-efficacy as a mediating variable. The study employs a quantitative approach, using the entire population as the sample (saturated sampling). Research data were collected from a combination of primary and secondary sources, involving 39 respondents. Data analysis was conducted using IBM SPSS version 25. The results indicate that: (1) accounting competencies positively affect work readiness, (2) accounting competencies positively influence self-efficacy, (3) self-efficacy has a positive impact on work readiness, and (4) self-efficacy serves as a mediating variable between accounting competencies and work readiness. For future research, it is recommended to expand the scope of variables to provide a more comprehensive understanding.